Impact of statin-ezetimibe combination on coronary atheroma plaque in patients with and without chronic kidney disease — Sub-analysis of PRECISE-IVUS trial. (1st October 2018) - Fujisue, Koichiro; Nagamatsu, Suguru; Shimomura, Hideki; Yamashita, Takuro; Nakao, Koichi; Nakamura, Sunao; Ishihara, Masaharu; Matsui, Kunihiko; Yamamoto, Nobuyasu; Koide, Shunichi; Matsumura, Toshiyuki; Fujimoto, Kazuteru; et al.
Abstract: Background: Chronic kidney disease (CKD) deteriorates the prognosis of patients undergoing percutaneous coronary intervention (PCI). Because coronary artery disease (CAD) is the major cause of death in CKD patients, cardiovascular risk reduction has been clinically important in CKD. We hypothesized intensive lipid-lowering with statin/ezetimibe attenuated coronary atherosclerotic development even in patients with CKD. Methods: In the prospective, randomized, controlled, multicenter PRECISE-IVUS trial, 246 patients undergoing intravascular ultrasound (IVUS)-guided PCI were randomly assigned to receive atorvastatin/ezetimibe combination or atorvastatin alone (the dosage of atorvastatin was up-titrated to achieve the level of low-density lipoprotein cholesterol < 70 mg/dL). Serial volumetric IVUS findings obtained at baseline and 9–12 month follow-up to quantify the coronary plaque response in 202 patients were compared stratified by the presence or absence of CKD. Results: CKD was observed in 52 patients (26%) among 202 enrolled patients. Compared with the non-CKD group, the CKD group was significantly older (71.5 ± 8.6 years vs. 64.4 ± 9.6 years, P < 0.001) with similar prevalence of comorbid coronary risk factors and lipid profiles. Similar to the non-CKD group (−1.4 [−2.8 to −0.1]% vs. −0.2 [−1.7 to 1.0]%, P = 0.002), the atorvastatin/ezetimibe combination significantly reduced ∆PAV compared with atorvastatin alone even in the CKD group (−2.6 [−5.6 to −0.4]% vs. −0.9 [−2.4 to 0.2]%, P = 0.04). Conclusions: As with non-CKD, intensive lipid-lowering therapy with atorvastatin/ezetimibe demonstrated stronger coronary plaque regression effect even in patients with CKD compared with atorvastatin monotherapy. Trial registration:NCT01043380 (ClinicalTrials.gov ). Highlights: Dual lipid-lowering therapy (DLLT) strongly reduced LDL cholesterol. DLLT reduced coronary plaque in chronic kidney disease (CKD) patients. DLLT inhibits cholesterol absorption in patients with CKD. Inhibition of cholesterol absorption related to coronary plaque volume change